Flow-Mediated Dilatation: Learning Curve Study with a Novice Operator - Arko S. Dhar; Marie Fisk; Carmel M. McEniery; Domonkos Cseh (Artery Research)
Abstract Background Performing reproducible flow-mediated dilatation (FMD) measurements can be challenging, especially among inexperienced operators. Our aim was to present the detailed learning curve of a novice operator. Methods Following a one-week basic training period, the operator performed duplicate measurements on 6–8 individuals per week, for six weeks. The operator followed the recommendations of the most recent guideline. Duplex ultrasound was used for the simultaneous and continuous measurement of brachial artery diameter and local blood flow velocity. Following a 1-min recording of baseline diameter (D), FMD was measured after a 5-min period of occlusion of the proximal forearm vessels. Inter-session coefficient of variation (CV) values for D and FMD were calculated for each week. Results The number of volunteers assessed each week were the following: 8, 7, 7, 6, 7, 7 individuals. CV values for both D and FMD exhibited a decreasing trend over the training period, ending at 1.73% for D and 14.24% for FMD at week 6. These CV values are within the range outlined in the most recent FMD guideline for proficiency. Conclusion Within a reasonable timeframe, and with careful adherence to measurement guidelines, the attainment of sound reproducibility in FMD measurements by a novice operator is feasible.